The Dual Nature of Blood: Transfusion-Mediated Immunomodulation in Modern Medicine (Sir Salimullah Medical College Journal, 2026)
Allogeneic blood transfusion is a life-saving intervention that carries a significant, though often overlooked, immunologic consequence. Known as Transfusion-Mediated Immunomodulation (TRIM), this phenomenon represents a constellation of immune alterations in the recipient, ranging from beneficial tolerance to harmful immunosuppression and inflammation. Historically recognized for improving kidney transplant survival, the modern understanding of TRIM primarily characterizes it as a deleterious event that increases the risk of postoperative infections, organ failure, and potentially cancer recurrence. The pathophysiology has evolved from a focus on donor leukocytes to the complex “storage lesion,” involving soluble biological mediators, extracellular vesicles, and mitochondrial DNA released during blood product storage. While universal leukoreduction has mitigated the risk, it has not eliminated it. This review delineates the key mechanisms driving TRIM, critically evaluates the strength of clinical evidence linking it to adverse outcomes, and champions Patient Blood Management as the cornerstone strategy for safeguarding patients against its effects.Sir Salimullah Med Coll J 2025; 33: 3-6